2011
DOI: 10.1152/ajprenal.00546.2010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial proliferation and mesenchymal transition contribute to vascular rarefaction following acute kidney injury

Abstract: Acute kidney injury induces the loss of renal microvessels, but the fate of endothelial cells and the mechanism of potential vascular endothelial growth factor (VEGF)-mediated protection is unknown. Cumulative cell proliferation was analyzed in the kidney of Sprague-Dawley rats following ischemia-reperfusion (I/R) injury by repetitive administration of BrdU (twice daily) and colocalization in endothelial cells with CD31 or cablin. Proliferating endothelial cells were undetectable for up to 2 days following I/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
256
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 258 publications
(268 citation statements)
references
References 51 publications
(65 reference statements)
8
256
0
4
Order By: Relevance
“…Progressive tubulointerstitial fibrosis is the hallmark of AKI‐to‐CKD progression. In agreement with previous studies 28, 30, 31, we observed that both NX‐IRI and BI‐IRI led to increased renal fibrosis following AKI. It was noteworthy that BI‐IRI also caused slightly but significantly increased collagen accumulation at 5 weeks after AKI regardless of no significantly increase in Scr compared with sham, indicating that the histological change of kidney tissues might precede the decline of biochemistry parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Progressive tubulointerstitial fibrosis is the hallmark of AKI‐to‐CKD progression. In agreement with previous studies 28, 30, 31, we observed that both NX‐IRI and BI‐IRI led to increased renal fibrosis following AKI. It was noteworthy that BI‐IRI also caused slightly but significantly increased collagen accumulation at 5 weeks after AKI regardless of no significantly increase in Scr compared with sham, indicating that the histological change of kidney tissues might precede the decline of biochemistry parameters.…”
Section: Discussionsupporting
confidence: 93%
“…11,12 Because of their limited replicative capacity, renal ECs are thought to be insufficiently capable to completely repair the injured endothelium of the peritubular capillary plexus after IRI. 13,14 Therefore, current therapeutic strategies to prevent microvascular loss have focused on the prevention of pericyte perturbation to reduce capillary rarefaction. [15][16][17][18] However, once rarefaction has occurred, these strategies may fail to induce sufficient revascularization required to reverse renal dysfunction.…”
mentioning
confidence: 99%
“…Research over the past decade has provided substantial data showing that AKI leads to CKD (2)(3)(4)(5)(6)(7)(8). Although the exact mechanisms underlying the progression from AKI to CKD continue to be explored, endothelial damage may play a critical role in outcomes, leading to nephron drop-out, interstitial fibrosis, and, ultimately, CKD (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). A full review of the data on the link between AKI and CKD in animals and adults is beyond the scope of this article but has recently been performed (5).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Acute kidney injury (AKI) has emerged as a risk factor for future CKD in both pediatric (2,3) and adult observational studies (4,5). Animal models have begun to identify the pathophysiologic mechanisms that lead to the development of CKD after episodes of AKI (5)(6)(7)(8). While there has been significant progress in studying the short-term implications of AKI in neonates, numerous critical gaps in our understanding of the epidemiology of neonatal AKI and the future development of CKD remain.…”
Section: Introductionmentioning
confidence: 99%